Are rare heterozygous SYNJ1 variants associated with Parkinson’s disease? - Konstantin Senkevich; Sitki Cem Parlar; Cloe Chantereault; Eric Yu; Jamil Ahmad; Jennifer A. Ruskey; Farnaz Asayesh; Dan Spiegelman; Cheryl Waters; Oury Monchi; Yves Dauvilliers; Nicolas Dupré; et al. (npj Parkinson's Disease)
Abstract Previous studies have established that rare biallelic SYNJ1 mutations cause autosomal recessive parkinsonism and Parkinson’s disease (PD). We analyzed 8165 PD cases, 818 early-onset-PD (EOPD, < 50 years) and 70,363 controls. Burden meta-analysis revealed an association between rare nonsynonymous variants and variants with high Combined Annotation-Dependent Depletion score (> 20) in the Sac1 SYNJ1 domain and PD (Pfdr = 0.040). A meta-analysis of EOPD patients demonstrated an association between all rare heterozygous SYNJ1 variants and PD (Pfdr = 0.029).